2022
DOI: 10.3390/foods11172681
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Interaction between Starchy Polyelectrolyte Layers for Adjusting Protein Release from Nanocapsules in a Simulated Gastrointestinal Tract

Abstract: Orally delivered bioactive proteins face great challenges in the harsh environment of the upper gastrointestinal tract (GIT) in the field of functional foods based on bioactive proteins. Therefore, it is necessary to design carriers and delivery systems that have the potential to overcome the problem of lower bioaccessibility for protein cargoes. In this work, we present a starchy oral colon-targeting delivery system, capable of improving the release profile of the protein cargoes. The starchy oral colon-targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…As shown in Figure 3c,d, the values of the exponent constant n of MRPs in SGF and SIF were 0.7451 and 0.6945, respectively, while those of MRPL were 1.0307 and 0.9096, respectively, which suggested that the release of MRPs in vitro was diffusion coupled with erosion, while that of MRPL was mainly erosion. Moreover, the K value of MRPL was smaller than that of MRPs, both in SGF and SIF, indicating that the release rate of MRPL was much slower due to the protective effect of liposome embedding [39]. 4a,b, MRPs and MRPL all exhibited inhibitory effects on the survival of MKN-28 and HepG-2 cells with a dose-dependent manner.…”
Section: Cell Viabilitymentioning
confidence: 92%
“…As shown in Figure 3c,d, the values of the exponent constant n of MRPs in SGF and SIF were 0.7451 and 0.6945, respectively, while those of MRPL were 1.0307 and 0.9096, respectively, which suggested that the release of MRPs in vitro was diffusion coupled with erosion, while that of MRPL was mainly erosion. Moreover, the K value of MRPL was smaller than that of MRPs, both in SGF and SIF, indicating that the release rate of MRPL was much slower due to the protective effect of liposome embedding [39]. 4a,b, MRPs and MRPL all exhibited inhibitory effects on the survival of MKN-28 and HepG-2 cells with a dose-dependent manner.…”
Section: Cell Viabilitymentioning
confidence: 92%
“…Metallic nanoparticles present opportunities to enhance central nervous system (CNS) drug delivery through strategies like functionalization with transcytosis ligands [10]. For example, intranasally administered fentanyl loaded in transferrin-conjugated nanoparticles exhibited rapid transport into the brain, providing prolonged pain relief in preclinical models [36]. The transferrin ligand enabled brain permeability by binding transferrin receptors onto nasal epithelial cells.…”
Section: Neurological Disordersmentioning
confidence: 99%
“…Li et al fabricated a type of oral starchy colon-targeting delivery system, which could be used to improve the bioaccessibility of bioactive insulin. By using layer-by-layer assembly of starchy polyelectrolytes (carboxymethyl anionic starch and spermine cationic starch) onto the surface of insulin nanoparticles via electrostatic interaction, insulin nanoparticles could be protected from degradation by digestive fluids, thus avoiding their burst release in simulated gastric and intestinal fluids [ 2 ].…”
mentioning
confidence: 99%